1991
DOI: 10.1093/ajcn/54.5.884
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of plasma retinol, β-carotene, and α-tocopherol during adolescence

Abstract: The relationships of plasma retinol, retinol-binding protein (RBP), beta-carotene, and alpha-tocopherol with their potential determinants, plasma cholesterol and triglyceride, body fat, dietary intake, stages of pubertal development, and drugs, were examined in a French sample of 263 boys and 246 girls aged 10-15 y. By use of multiple-regression analysis, plasma retinol concentration was positively related to plasma cholesterol and triglyceride, sexual-maturation index, body fat, and being male. For plasma RBP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
1
2

Year Published

1992
1992
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 28 publications
4
13
1
2
Order By: Relevance
“…Vitamin A has also been correlated in a direct, linear way with plasma concentrations of total lipids among the group of children with IDDM (n ¼ 47, r ¼ 0.36, P < 0.02). Herbeth et al (1991) obtained similar results in healthy children aged 10 -15 y. These results suggest that RBP performs a protective function in situations of hypertriglyceridemia or atherogenic risk, perhaps in order to improve the transport of retinol (diminished) as an antioxidant to where it is required, or perhaps for some other important, but as yet unknown, function.…”
Section: Influence Of Metabolic Control Of the Illness On Atherogenicsupporting
confidence: 59%
“…Vitamin A has also been correlated in a direct, linear way with plasma concentrations of total lipids among the group of children with IDDM (n ¼ 47, r ¼ 0.36, P < 0.02). Herbeth et al (1991) obtained similar results in healthy children aged 10 -15 y. These results suggest that RBP performs a protective function in situations of hypertriglyceridemia or atherogenic risk, perhaps in order to improve the transport of retinol (diminished) as an antioxidant to where it is required, or perhaps for some other important, but as yet unknown, function.…”
Section: Influence Of Metabolic Control Of the Illness On Atherogenicsupporting
confidence: 59%
“…This increase probably reflects larger liver vitamin A stores that reflect normal physiological changes with growth and does not necessarily indicate better vitamin A status with ageing. Plasma concentrations of retinol and RBP increase greatly during adolescence (particularly during puberty) with the degree of sexual maturation in boys and girls, even after adjusting for plasma cholesterol and TAG concentrations (Herbeth et al, 1991). Consequently, by using single cutoff points of plasma retinol concentration for all ages (eg 0.70-1.05 mmol/l), there is a greater likelihood of those aged 4-6 y being falsely considered to have suboptimal vitamin A status compared with those aged 15-18 y.…”
Section: Discussionmentioning
confidence: 99%
“…It is well documented that the growth velocity during adolescence is slower in undernourished populations (Eveleth and Tanner, 1990), giving rise to cephalopelvic disproportion which, in the adolescents who become pregnant, is related to increased maternal and foetal mortality (Harrison et al, 1985). It has also been suggested that iron is an essential nutrient for skeletal growth (Herbeth et al, 1991) and, thus, iron de®ciency may be a limiting factor for growth during adolescence (Brabin and Brabin, 1992). In Bangladesh, almost a quarter of the total population are adolescents.…”
Section: Introductionmentioning
confidence: 99%